PRESENTATION SKILL TRAINING FOR THE PRODUCT RESELLERS ZORAYA IN BANDUNG - Rini Anisyahrini; Winne Wardhiani; Vikry Abdul Rahiem; Sutrisno Sutrisno (Pasundan International of Community Services Journal (PICS-J), 2019)
Indonesia has the perpetrators of Micro, Small and Medium Enterprises or SMEs which sums are growing. In the city of Bandung there Zoraya Community consisting of small and medium entrepreneurs, which aims to share the products and exchange experiences in marketing their products. Zoraya Community members belong to the cottage industry entrepreneurs, who have problems in marketing their products. Marketing through social media and direct marketing or direct selling them often become a bottleneck. This occurs at the time of product exhibition,they are hampered in communicating to consumers in promoting their products. The right solution to the problem is the public speaking training, capacity building through presentation skills, facilitation process of direct selling products during the exhibition. The method used in the form of training activities as part of the presentation skill of public speaking, presentations skills training benef its, training of basic techniques for presentation public speaking skills, and training make the script about a superior product. The results of this activity is that participants increased understanding of how effective product presentation and systematic. Besides increasing the confidence member Zoraya Community after being given training.